The effects of altitude training on hormonal response in professional cyclists - Faiss, R.; Krumm, B.; Moreillon, B.; Mettraux, L.; Wackernell, J.; Spragg, J.; Faulhaber, M. (Current Issues in Sport Science, 2025)
Introduction